Evaluation of Ricinus communis as a phytoremediator of manganese in soil contaminated with sewage sludge - Patek Mohd, Nur Nazirah; Abdu, Arifin; Jusop, Shamsuddin; Karim, Md. Rezaul; Muhammad Nazrin,; Basri, Mohd Hadi Akbar; Jamaluddin, Aiza Shaliha (Universiti Putra Malaysia Press, 2017)
The cost to dispose of sludge is very high, and Malaysia usually treats it by composting. However, composting is not a feasible method because it is time consuming. The application of sewage sludge on cropland is economical method because it provides the plant nutrients. However, it has a serious impact on the plants, animal and environment due to high concentration of heavy metals. Therefore, phytoremediation is a green technology to remove pollutants especially heavy metals from contaminated soil. This study was conducted to determine the potential of Ricinus communis to remove heavy metal in soil. The seedlings were planted on six different planting media T0 (100% soil-Control), T2 (80% soil + 20% sewage sludge), T3 (60% soil + 40 % sewage sludge), T4 (40% soil + 60% sewage sludge), T5 (20% soil + 80% sewage sludge) and T6 (100% sewage sludge). The highest accumulation of Mn was observed in leaves. Ricinus communis were found to be suitable as phytoremediators to clean heavy metals especially Mn as its TF value was higher than BCF.